2023
DOI: 10.1097/ms9.0000000000000621
|View full text |Cite
|
Sign up to set email alerts
|

A 5-year retrospective study of intraocular pressure control after trabeculectomy: a retrospective cohort study

Abstract: Background: Glaucoma is a group of diseases that damage the optic nerve in the eye, resulting in vision loss and, in severe cases, blindness. The prevalence of glaucoma and glaucoma blindness is highest in West Africans. Objective: The study presents a 5-year retrospective analysis of intraocular pressure (IOP) and complications after trabeculectomy. Materials and methods: Trabeculectomy was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Although a 100% success was not achieved in this study, our data showed good management outcomes, which are comparable to similar studies that reported a good response to the management strategies [22,26] . Moore's ulcer, like cataracts [27] and glaucoma [28] , poses a possible blindness danger that is being treated and controlled in our facility with the goal of providing holistic eye care. The major challenge in managing Mooren's ulcer perforations with patch graft is the recurrence of the ulcer in grafted material [20,24] .…”
Section: Discussionmentioning
confidence: 99%
“…Although a 100% success was not achieved in this study, our data showed good management outcomes, which are comparable to similar studies that reported a good response to the management strategies [22,26] . Moore's ulcer, like cataracts [27] and glaucoma [28] , poses a possible blindness danger that is being treated and controlled in our facility with the goal of providing holistic eye care. The major challenge in managing Mooren's ulcer perforations with patch graft is the recurrence of the ulcer in grafted material [20,24] .…”
Section: Discussionmentioning
confidence: 99%